(untitled) (ModaPalavra e-periódico, 2013)
The tecidoteca offers a collection of textile flags for consultation and research community, students and professionals in the clothing and fashion, which supports a better understanding and aid in the development of academic and development of seasonal collections of fashion. The methodology used for the preparation of textile flags are: description, handling, cutting, burning and laboratory tests carried out in partnership with textile lab control 1 and 2 in the control of Goioerê Regional Campus. This extension project becomes an important tool for the sharing of information and knowledge available in different media, in this case the collection of woven, non woven, knitted fabrics, color palette and commercial catalogs.